The Pedagogical Internalization of Hadith on Communication Ethics: An Islamic Educational Strategy for Countering Digital Disinformation and Cyberbullying - Irfa Waldi; Syah Wardi; Rizkika Walda Lubis; Nur Habibah (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study is driven by the increasing crisis of digital disinformation and cyberbullying, which reflects a systemic decline in communication ethics within online ecosystems. It aims to reconceptualize Hadith-based communication ethics as a pedagogical framework in Islamic education to address these challenges. The study employs a qualitative library research method through thematic analysis of Sahih al-Bukhari and Sahih Muslim. The findings identify three main prophetic communication principles: justice (al-‘adl), contextual appropriateness (al-maqām), and tolerance (al-hanifiyyah as-samhah). The main contribution of this study is the formulation of “Prophetic Digital Ethics,” an integrative framework that operationalizes classical Hadith values into digital communication governance. This framework is implemented through pedagogical strategies such as digital case analysis, cyber-conflict simulation, and counter-narrative training to strengthen verification literacy and ethical discourse. The study concludes that prophetic communication ethics provide a strong normative and pedagogical foundation for mitigating misinformation, online hate, and cyberbullying, while fostering ethical, critical, responsible, and socio-religiously moderate digital citizenship.